The challenges of midlife women: themes from the Seattle midlife Women's health study - Annette Joan Thomas; Ellen Sullivan Mitchell; Nancy Fugate Woods (BMC, 2018)
Abstract Background Midlife, the period of the lifespan between younger and older adulthood, has been described as a period of transition in women's lives. Investigators studying midlife have focused on women 40 to 65 years of age, who typically experience multiple social, psychological and biological challenges, among them the menopausal transition. Investigators have reported a diverse array of stressful events, for example, health concerns, family problems, work-related issues, deaths, frustrated goal attainment, and financial worries; however, none have identified which life events midlife women experience as the most salient. The purpose of this study was to understand the meaning behind the experiences that midlife women identify as the most challenging. Methods Participants were enrolled in The Seattle Midlife Women's Health Study, a longitudinal study spanning up to 23 years. Summative content analysis, incorporating manifest and latent analysis approaches, was used to identify life experiences that women described as the most challenging looking back over 15 years of being in the study. Eighty-one women responded to the question, "Since you have been in our study (since 1990 or 1991), what has been the most challenging part of life for you?" Results Women identified the most challenging aspects of midlife as changing family relationships, re-balancing work/personal life, re-discovering self, securing enough resources, and coping with multiple co-occurring stressors. Within these themes the most frequently reported challenges were: multiple co-occurring stressors, divorce/breaking up with a partner, health problems of self, and death of parents. Few women mentioned menopause as the most challenging aspect of their lives. Conclusion Women found themselves searching for balance in the midst of multiple co-occurring stressors while coping with losses and transitions, for some in a context of limited resources. Menopause was infrequently mentioned. Future research to identify the challenges experienced by more diverse populations of women and further understanding of the dynamics among multiple co-occurring stressors is needed to provide individualized health care appropriately to midlife women.